Comparison of outcome of Desarda versus Bassini repair in management of complicated inguinal hernia - Ansari, Faiz Manzar; Hameed, Tariq; Jain, Sudhir Kumar; Dua, Amrita; Nizam, Adiba (International Surgery Journal, 2019)
Background: Complicated inguinal hernia is a common problem faced by surgeons across the world. Various methods of surgical repair have been described. It is important to identify the best repair technique of inguinal hernia to have better post-operative outcome. Methods: This randomised controlled study consisted of 84 cases of complicated inguinal hernias presenting to surgical emergency department of Maulana Azad Medical College. Patients were randomly allocated to two repair groups- Desarda and Bassini and various intra/post-operative parameters were compared. Results: Duration of surgery and postoperative pain scores were less in Desarda group. Time to return to strenuous daily activities was also less with Desarda repair. Desarda repair was associated with less incidence of chronic inguinodynia and post-operative complications. Conclusions: Desarda repair was found to be superior to Bassini group due to shorter duration of surgery. Patients required less analgesics following Desarda repair as compared to Bassini group. There was no recurrence in any group at four months follow up.